Gamma Interferon Fails To Induce Expression of Indoleamine 2,3-Dioxygenase and Does Not Control the Growth of Chlamydophila abortus in BeWo Trophoblast Cells - Entrican, Gary (American Society for Microbiology, 2002)

(untitled)
The BeWo trophoblast cell line does not constitutively express the tryptophan degrading enzyme indolamine 2,3-dioxygenase (IDO), nor can IDO expression be induced by gamma interferon. This correlates with the inability of BeWo cells to control the growth of Chlamydophila abortus, in contrast to effects observed in HeLa cells treated with gamma interferon.